PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA DI PT HOHO MARAPOYAN - Alexsander Putra; Rina Selva Johan; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: Price is the amount of money being exchanged for a product or service. promotion of an activity to increase consumer demand for products offered by producers or sellers. A purchase decision is an action taken by an individual or a group to select any of the goods / services desired. This study aims to determine the effect of price and promotion on purchase decisions. The population in this study are the buyers of Honda motorcycles in PT Hoho and respondents drawn are buyers for teens and adults who have a family, and the respondents are consumers directly and no middleman others, using sampling techniques through simple random sampling method. Data were collected using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, t test and F test with significance level of 0.05%. Based on the research showed that prices and promotions simultaneously positive and significant influence on purchasing decisions. It is based on the analysis results, which show the calculation results F count> F table (100.328> 3.159). Furthermore, by t test to determine whether each of the independent variables affect the dependent variable. The results partially show a significant effect on the price of the purchase decision. This is evidenced in which the t (4.394)> t table (2.002). Furthermore, for the promotion variables showed that significantly influence the decision pebelian. This is evidenced in which the t (7.868)> t table (2.002). The predictive ability of these two variables on purchase decisions in the study of 77.9% (R Square .779) while the remaining 22.1% is influenced by other factors which are not included in this study.Key Words: price, promotion, and buying decision